2010
DOI: 10.5713/ajas.2010.90394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium-enriched Japanese Radish Sprouts and Rhodobacter capsulatus on the Cholesterol and Immune Response of Laying Hens

Abstract: :Immune response and yolk cholesterol are crucial factors for commercial chicken producers. The objectives of this study were to investigate the effect of selenium-enriched Japanese radish sprouts (Se-enriched JRS) and R. capsulatus synergistically on immune response and cholesterol in laying hens. A total of 50 laying hens (20-wk old) were assigned to 5 dietary treatment groups, and fed diets supplemented with 2.5 μg/kg, 5 μg/kg, 10 μg/kg Se-enriched JRS and 5 μg/kg Se-enriched JRS+R. capsulatus (0.02%). Egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…An increased level of its HDL fraction in egg yolk and plasma of laying hens supplemented with nano-Se [20]. Incorporation of Se-enriched Japanese radish sprouts in feed led to increased HDL-C concentration and decreased triglyceride and cholesterol concentrations due to hypolipidemic effect of selenium by changing the excretion of cholesterol and bile acids [34]. The increased level of HDL-C in Group III could be attributed to inhibiting effect of curcumin on lipoprotein-α [61].…”
Section: Serum Lipid Pro Lementioning
confidence: 99%
“…An increased level of its HDL fraction in egg yolk and plasma of laying hens supplemented with nano-Se [20]. Incorporation of Se-enriched Japanese radish sprouts in feed led to increased HDL-C concentration and decreased triglyceride and cholesterol concentrations due to hypolipidemic effect of selenium by changing the excretion of cholesterol and bile acids [34]. The increased level of HDL-C in Group III could be attributed to inhibiting effect of curcumin on lipoprotein-α [61].…”
Section: Serum Lipid Pro Lementioning
confidence: 99%
“…Plasma Se significantly increased from a baseline of 96 ± 4 ng ml −1 to 110 ± 3 ng ml −1 after Se-enriched broccoli consumption, along with cytokines interleukin-2 and interleukin-4 production from participants' peripheral blood mononuclear cells when stimulated with phorbol 12-myristate 13-acetate and ionomycin, whilst no increases were observed following consumption of control broccoli (Figure 5 ). Additionally Se-enriched radish sprouts were found to be immune-stimulatory in hens (Hossain et al, 2010 ). In contrast, a study testing Se-enriched sauerkraut extracts on a macrophage cell line in vitro showed anti-inflammatory effects (Peñas et al, 2012 ), highlighting a major discrepancy between in vivo and in vitro studies.…”
Section: Selenoglucosinolates For Human Nutritionmentioning
confidence: 99%
“…Another source of organic Se is Se-enriched plants. Supplementation of Se from Se-enriched garlic (Allium sativum), cabbage (Brassica pekinensis L.) [10], bean sprout (Vigna radiate) [11], and Japanese radish sprout (Raphanus sativus) [12] gave some positive responses in broilers and layers. The aforementioned findings demonstrate that Se from Se-enriched plants is an alternative Se source in poultry diets.…”
Section: Introductionmentioning
confidence: 97%